2011
DOI: 10.4239/wjd.v2.i7.114
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the story of protein misfolding in diabetes mellitus

Abstract: Both environmental and genetic factors contribute to the development of diabetes mellitus and although monogenic disorders are rare, they offer unique insights into the fundamental biology underlying the disease. Mutations of the insulin gene or genes involved in the response to protein misfolding cause early onset diabetes. These have revealed an important role for endoplasmic reticulum stress in β-cell survival. This form of cellular stress occurs when secretory proteins fail to fold efficiently. Of all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…␤-cells are specialized for the manufacture of proinsulin, yet highly up-regulated proinsulin synthesis as occurs in early type 2 diabetes promotes proinsulin misfolding and ER stress (4,(33)(34)(35)(36)(37). MIDY mutants offer an opportunity to study the effects of proinsulin misfolding on ␤-cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…␤-cells are specialized for the manufacture of proinsulin, yet highly up-regulated proinsulin synthesis as occurs in early type 2 diabetes promotes proinsulin misfolding and ER stress (4,(33)(34)(35)(36)(37). MIDY mutants offer an opportunity to study the effects of proinsulin misfolding on ␤-cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in β cells, the ER is the site of insulin biosynthesis (Harding and Ron, 2002 ). The notion of ER stress in diabetes originated after several studies concluded that during the pre-diabetic period, β cells entered a hyper-active mode of pro-insulin synthesis, which led to an increase in protein misfolding; the mis-folded proteins eventually accumulated at the ER and caused ERS (Kaufman, 2002 ; Dobson, 2003 ; Sitia and Braakman, 2003 ; Thomas et al, 2011 ; Kim et al, 2012 ).…”
Section: Ers and Mitochondrial Functionmentioning
confidence: 99%
“…Evidence is accumulating that subtle perturbations of insulin biosynthesis (due either to variant insulin genes or mutations in the ER folding machinery) may contribute to the pathogenesis of non‐syndromic Type 2 DM in humans [111,112] as in the Akita mouse [17,113]. A newly recognized biophysical contribution to such β‐cell dysfunction is “molecular crowding” in the ER due to over‐expression of nascent proinsulin in the face of peripheral insulin resistance [114], a concept that may have therapeutic implications [33].…”
Section: Diabetes‐associated Mutationsmentioning
confidence: 99%